1984
DOI: 10.1007/bf01129615
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing the success of in vitro fertilization for alleviating human infertility

Abstract: The program for in vitro fertilization at Bourn Hall began in October 1980. Various types of infertility have been treated during this time using the natural menstrual cycle or stimulation of follicular growth with antiestrogens and gonadotrophins. Follicular growth and maturation are assayed by urinary estrogens and LH, monitored regularly during the later follicular stage. Many patients had an endogenous LH surge; others needed an injection of HCG to induce ovulation. All oocytes were recovered by laparoscop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
121
1
18

Year Published

1985
1985
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 418 publications
(146 citation statements)
references
References 43 publications
6
121
1
18
Order By: Relevance
“…Since the first application of assited reproduction techniques, many factors have been associated with the outcome of IVF treatment [20]. Although all the patients were exposed to the same IVF protocol in follicular stimulation, follicular responses among the patients differed significantly.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the first application of assited reproduction techniques, many factors have been associated with the outcome of IVF treatment [20]. Although all the patients were exposed to the same IVF protocol in follicular stimulation, follicular responses among the patients differed significantly.…”
Section: Discussionmentioning
confidence: 99%
“…A good quality oocyte is essential for maturation, fertilization and post-embryonic development. Edwards et al (1984) reported that fertilization rates were higher with mature oocytes and Tesarik et al (1995) found that addition of estradiol to human oocyte maturation medium increased the fertilization and cleavage rates of in-vitro matured oocytes [20,21].…”
Section: Discussionmentioning
confidence: 99%
“…An association between embryos' cleavage rate and morphologic characteristics, and their ability to implant has been reported soon after the first live birth using IVF, and development of controlled ovarian hyperstimulation protocols [3][4][5]. Since then, a multitude of morphologic parameters associated with increased viability of pronuclear, cleavage stage, and blastocyst stage embryos were identified, and numerous embryo grading systems have been developed [6][7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…This is usually achieved either by the extended culture of human embryos to the blastocyst stage [5,6] or by the morphological analysis and selection of the highest quality embryos for transfer [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22]. More recently, the assessment of zygote quality has been applied [23][24][25][26][27][28][29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%